2008
DOI: 10.1097/jsm.0b013e318160c05d
|View full text |Cite
|
Sign up to set email alerts
|

Scapular Muscular Activity With Shoulder Impingement Syndrome During Lowering of the Arms

Abstract: These findings pointed out the importance of evaluating the lowering of the arms in individuals with IS and suggested that measures of coactivation, besides reflecting the real purpose of the muscular actions during functional activities, are more sensitive to detect changes between groups. The evaluation of the coactivation of the middle trapezius/serratus anterior should be included in clinical assessment of individuals with IS and investigations on the etiology and progression of IS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 21 publications
0
44
0
2
Order By: Relevance
“…Borstad and Ludewig (2002) compared three-dimensional scapular kinematics during elevation and lowering of the arm in subjects with and without SIS, and group differences tended to be magnified in the eccentric phase in this study. Lower coactivation of the middle trapezius/serratus anterior muscles was found in subjects with SIS when compared to controls during lowering of the arm (de Morais Faria et al 2008). …”
Section: Introductionmentioning
confidence: 94%
“…Borstad and Ludewig (2002) compared three-dimensional scapular kinematics during elevation and lowering of the arm in subjects with and without SIS, and group differences tended to be magnified in the eccentric phase in this study. Lower coactivation of the middle trapezius/serratus anterior muscles was found in subjects with SIS when compared to controls during lowering of the arm (de Morais Faria et al 2008). …”
Section: Introductionmentioning
confidence: 94%
“…The number of muscles contributing to movement and the degrees of freedom of motion make the study of motor control at the shoulder extremely difficult. Several authors have described the timing of shoulder muscle activation onset during arm motions [5,22,54], others have reported muscle activation magnitudes [8,31], while some have reported the ratio of activation magnitude for several pairs of synergistic muscles at the shoulder [7,8]. All of these efforts have contributed valuable knowledge of how the neuromuscular system controls motion at the shoulder complex.…”
Section: Introductionmentioning
confidence: 99%
“…If the loaded tissue is unable to manage or adapt, pathology may result. Biomechanical faults may originate through repetitive movement patterns that gradually alter tissue extensibility or from neuromuscular activation alterations secondary to a stimulus such as pain [7,8,32,38]. Neuromuscular alterations are particularly problematic as they can interfere with the complex timing and muscle synergies that are critical to shoulder movement [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Scapulothoracic muscle weakness is a cause of scapular instability and contributes to secondary subacrominal impingement syndrome 1,4,5) . In athletes or workers who perform repeated overhead movements, shoulder muscle fatigue may result from shoulder pathologies 6 , 7 ) , and muscle imbalance caused by acute muscle fatigue may impede normal muscular activation 8,9) . Several studies have revealed the importance of scapular muscle strength, neuromuscular control and scapular stability for normal shoulder functioning 4,10,11) .…”
Section: Introductionmentioning
confidence: 99%